Selection of V-Belt for Power Transmission in Agricultural Machinery (Progressive Agriculture, 2013)
The solution of a v-belt design problem depends upon many data tables, figures, equations and sequence of calculations. To solve such a problem a computer program is developed which facilitates the design procedure by fast computation with less drudgery and more accuracy. Computed result shows the diameter of smaller and larger sheave, center distance, belt length, belt number, required number of belt, belt cross-section, as output after calculation. The computer-generated output by using this program is found more accurate and efficient than the conventional calculation method.DOI: http://dx.doi.org/10.3329/pa.v19i2.16961 Progress. Agric. 19(2): 187 - 194, 2008